Analysis of flow pattern transition from segregated to slug flow in upward inclined pipes. (June 2019) - Fan, Yilin; Pereyra, Eduardo; Sarica, Cem; Schleicher, Eckhard; Hampel, Uwe
Highlights: Experimental study was conducted to investigate the flow pattern transition from segregated to slug flows step by step. The difference between pseudo-slug and conventional slug flows was discussed by analyzing high-speed videos, 2-D and 3-D wire-mesh sensor data illustration, and structure characteristics. Experimental data shows that the structure velocity can be used as an indicator for the flow pattern transition from conventional slug to pseudo-slug flows. New approaches were proposed to model pseudo-slug structure velocity. Abstract: Segregated and slug flows are two of the most common flow patterns encountered in two-phase upward inclined pipe flow. However, the transition between them is ambiguous. Coherent and distinctive structures have been observed within the transition. These structures have been classified as pseudo-slug flow. The nature of pseudo-slug flow is not well understood due to the complexity of the structure. At low liquid loading conditions, this flow pattern can occupy a large operating region and cannot be neglected. This paper presents a detailed experimental work conducted in a facility with a valley configuration, focusing on the transition region between segregated and slug flows. Wire-mesh sensors were employed to investigate the liquid phase distribution within the flow structure. The current paper investigates the flow patterns and their transition in upward inclined pipe from different perspectives. The investigation includes analysis of images from high-speed videos, evaluation of 2-D liquid holdup axial evolution, 2-D liquid holdup distribution at pipe cross-section, 3-D interfacial structure evolution, and analysis of pressure gradient and liquid holdup measurement, flow characteristics, etc. Differences between slug and pseudo-slug flows are also presented. Three superficial liquid velocities (0.001, 0.005 and 0.01 m/s) and five inclination angles (2°, 5°, 10°, 15°, and 20°) are studied. Simplified correlations are proposed for pseudo-slug structural velocity, showing fair agreement.